Correlation of Serum Vitamin-D Level with Coronary Angiographic Severity In Patients with Acute Coronary Syndrome - Siddiki, Kamruzzaman; Hoque, Md Harisul; Rahman, Md Mukhlesur; Khaled, Md Fakhrul Islam; Faruq, Fysal; Alam, Md Mashiul; Kabir, Md Ahsanul; Islam, Sayed Nazmul; Islam, Md Azharul; Zaman, SM Mustafa (University Heart Journal, 2021)
Background: Acute Coronary Syndrome includes to a group of conditions compatible with acute myocardial ischemia and/or infarction that are usually due to an abrupt reduction in coronary blood flow. In the last decade vitamin-D deficiency as a predisposing factor for coronary artery disease is in growing interest. Prospective studies give conflicting results regarding correlation of serum vitamin D level with coronary angiographic severity in patients with acute coronary syndrome. Objective: To study the correlation between serum vitamin-D level with coronary angiographic severity in patients with acute coronary syndrome. Methodology: This cross sectional observational study was done between November 2018 and October 2019. Total 71 patients with diagnosis of first incident of acute coronary syndrome in department of cardiology, BSMMU who were underwent coronary angiogram included in this study considering the inclusion and exclusion criteria. Vitamin D was measured by chemiluminescent immunoassay after collection of venous blood at Department of Biochemistry, BSMMU. Angiographic severity was assessed by using Gensini score. Statistical analyses were carried out by using the Statistical Package for Social Sciences version 23.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Results: The mean age was found 55.9±10.7 years with a range from 36 to 82 years. Majority (83.1%) patients were male. The male-female ratio was 4.9:1. Thirty (42.3%) of the patients had STEMI, 28(39.4%) had NSTEMI and 13(18.3%) had unstable angina. Negative correlation (r=-0.479; p=0.001) was found between serum vitamin D level and Gensini score in patients with acute coronary syndrome. Conclusion: In this study found that serum vitamin-D level is inversely correlated with angiographic severity in patients with acute coronary syndrome. University Heart Journal Vol. 17, No. 2, Jul 2021; 103-107